Early Childhood Disadvantage for Sons of Mexican Immigrants: Body Mass Index Across Ages 2–5. Issue 7 (September 2016) - Lawrence, Elizabeth; Mollborn, Stefanie; Riosmena, Fernando
Purpose: To distinguish the origins of higher weight status and determine when and why intra- and interracial/ethnic disparities emerge. Design: The study used a longitudinal analysis of the Early Childhood Longitudinal Study–Birth Cohort (ECLS-B). Setting: The study was conducted in the United States. Subjects: Participants were children of non-Hispanic white mothers and children of U.S.- and foreign-born mothers of Mexican origin from a nationally representative sample of children born in the year 2001 (N ≈ 3700). Measures: The Centers for Disease Control and Prevention growth charts determined sex- and age-specific weight status. Covariates were obtained from birth certificate records and parent interviews. Analysis: Frequencies, growth curve trajectories, and ordinary least squares regression examined body mass index (BMI) and obesity across survey waves. Results: Compared to their peers with non-Hispanic white mothers, children of Mexican-heritage mothers have higher average BMI and greater rates of obesity. The BMI of boys with Mexican-born mothers is higher relative to whites and children of U.S.-born Mexican mothers across early childhood, increasing sharply at about age 4.5 years. This divergence is driven by increases in the BMI of boys, as girls do not show the same growth. A number of measures, including descriptors of children's nutritional intake, lifestyle factors, and acculturation, do not explain the increased obesity rates among sons of Mexican mothers. Conclusion: Despite favorable perinatal health and weight, Mexican-American sons of foreign-born mothers show disadvantages in BMI that emerge close to the start of kindergarten.